Becoming a Nurse: Stories of Vulnerability - Jacobsen, Frode; Søvik, Margrethe; Synnes, Oddgeir (Narrative Works)

(untitled) (The University of New Brunswick, 2017)
This article sets out to analyze written stories of nursing students focusing on challenging situations from clinical practice The analysis involves looking at how the stories present various versions of being and becoming a nurse. On the one hand, this calls for an examination of what is found in the stories, narrative structures, linguistic devices, word choice and so on. On the other hand, it implies looking at what is not found by reflecting on notable absences from the stories. The analysis underscores that vulnerability is a prominent feature of these stories. The article stresses the importance of honouring the stories while at the same time advocating the use of narrative pedagogy to put the stories in a larger context and thus develop the student nurses’ narrative resources.